An Introduction to the Transition from Graduation to Work: Challenges and Strategies in the Asia Pacific and Beyond - Dhakal, Subas P.; Verma, P.; Nankervis, A.; Burgess, K. (Springer, 2019)
The concept and the importance of Graduate Work-Readiness (GWR) in the region is outlined. The objectives and structure of the book are discussed followed by the mapping of the countries to be studied, the analysis undertaken in each of the countries and the structure of the book. The chapter sets out the contribution of the book and includes a list of limitations associated with the approach taken.